Gross Motor Activity Comparison Fullday School and Regular of Elementary School Sumenep Through BMAT-R - Nordiansyah, Shally; Prasetyo, Dyas Andry (Universitas Negeri Semarang, 2020)
The schools that implement Full Day School will not optimally carry out activities outside of effective hours so that such a condition can affect the studentsÃ¢â‚¬â„¢ interests and talents related to motor skills at school. This study uses purposive sampling due to certain considerations, The calculation of T value was done by testing the significance of the difference between the two means derived from the distribution for the different samples.Ã‚Â To find out the results of the hypothesis test was by seeing the equal variances not assumed. Based on the table, it could be seen that the value of P value was 0.000, while the mean difference was -22.967. The hypothesis testing based on significance was that H0 was accepted if the significance was greater than 0.05. H0 was rejected if the significance was less than 0.05. The test conducted showed that the significance was smaller than 0.05, namely 0.000, so H0 was rejected, which means that there was a difference in the average motoric score of full day school and regular school students.